2020
DOI: 10.1001/jamanetworkopen.2020.0427
|View full text |Cite
|
Sign up to set email alerts
|

Association of Childhood Family Connection With Flourishing in Young Adulthood Among Those With Type 1 Diabetes

Abstract: IMPORTANCE Higher levels of childhood family connection have been associated with measures of adult flourishing or eudaimonic well-being, such as purpose, self-acceptance, positive relationships, and growth. However, this association has not been examined among those with childhood-onset chronic disease. OBJECTIVES To investigate whether higher levels of childhood family connection were associated with greater flourishing in young adulthood among those with type 1 diabetes and, secondarily, whether this associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
(156 reference statements)
2
7
0
Order By: Relevance
“…Reverse causation was ruled out by the temporal ordering of the data (suicidal ideation was measured after flourishing). Our findings demonstrated the negative associations of ACEs and discrimination with flourishing 37 39 , as well as the effect of flourishing on reducing suicidal ideation 18 , 19 . Results are larger in magnitude but consistent with previous studies, most of which used cross-sectional designs.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Reverse causation was ruled out by the temporal ordering of the data (suicidal ideation was measured after flourishing). Our findings demonstrated the negative associations of ACEs and discrimination with flourishing 37 39 , as well as the effect of flourishing on reducing suicidal ideation 18 , 19 . Results are larger in magnitude but consistent with previous studies, most of which used cross-sectional designs.…”
Section: Discussionsupporting
confidence: 60%
“…Flourishing-centered suicide prevention programs may be especially relevant to suicide attempts encountered in the emergency department setting given the high suicide rates of 178 per 100 000 person-years in the first three months after discharge and the lack of care coordination with the warm handoff 46 , 47 . Family-focused interventions, as promoted by the Institute of Medicine, may be pivotal to promoting flourishing by supporting family connections 37 , 48 . Equally important is to promote flourishing among physicians and healthcare workers who may encounter patients with suicidal ideation, as improving the personal growth and environmental mastery of physicians and healthcare workers may reduce their risks of burnout 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Details of the survey procedures have been previously reported 19,20 and are briefly summarized here. Eligible survey participants were active patients at the NBDC between 01/12/2015 and 30/11/2016, were 18.0 to <30.0 years of age on 01/12/2015 and had a diagnosis of type 1 diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…Research has found that childhood adversity is associated with lower levels of flourishing, while positive childhood experiences such as higher levels of family connection and parental warmth promote flourishing in children and adults [ 13 , 38 , 39 , 40 , 41 , 42 , 43 ]. Existing research on childhood experiences and flourishing has primarily been examined within Western contexts.…”
Section: Introductionmentioning
confidence: 99%